Adherence barriers to treatment of patients with cardiovascular diseases: A qualitative study - Mozhgan Kalantarzadeh; Hojatollah Yousefi; Mousa Alavi; Jahangir Maghsoudi (Iranian Journal of Nursing and Midwifery Research, 2022)
Background: Adherence to treatment is highly important in the management of Cardiovascular Diseases (CVD). Barriers to effective and long-term adherence to treatment by the patient make achieving care and treatment goals challenging. The aim of this study was to identify the adherence barriers to the treatment plan in patients with CVD. Materials and Methods: A qualitative content analysis study was conducted to explore the experience of patients, family caregivers, and healthcare professionals (n = 35) using qualitative content analysis. The study was carried out between 2019 and 2020 in Isfahan, Iran. Purposive sampling was performed. Data collection was conducted through in-depth interviews and semi-structured until data saturation. Graneheim and Landman content analysis was performed simultaneously with data collection. Results: After data analysis, 3 themes and 6 categories were identified and named. Themes (and categories) include “Patients unreadiness to change” (misunderstanding of conditions and consequences and deterrence cultural practices and beliefs); “gap in healthcare services” (lack of adequate support for patients and discordance between healthcare professionals); and “limited access to healthcare services” (limited physical access and financial burden). Conclusions: The findings of the present study can provide a framework for healthcare professionals to employ preventive strategies, reduce disease complications, decrease unhealthy behaviours, and increase prolonged adherence to treatment recommendations in patients with CVD.